Cellulose-based electrospun nanofiber membrane with core-sheath structure and robust photocatalytic activity for simultaneous and efficient oil emulsions separation, dye degradation and Cr(VI) reduction. (15th April 2021) - Lu, Wanli; Duan, Chao; Zhang, Yanling; Gao, Kun; Dai, Lei; Shen, Mengxia; Wang, Wenliang; Wang, Jian; Ni, Yonghao
Graphical abstract: Highlights: A photocatalytic cellulose-based β-FeOOH@MIL-100(Fe)/CeP ENM is fabricated for water purification. The ENM has a core-sheath structure with an ultrahigh loading of MIL-100(Fe) heterojunctions. The ENM delivers a simultaneous high removal of oils, dyes and Cr(VI) under high water flux. The hybrid ENM shows super wettability, robust photo-Fenton synergy and long-term reusability. Abstract: Electrospun nanofiber membrane (ENM) shows great advantage and potential in wastewater treatment due to its unique properties. However, exploring a green and efficient ENM for remediation of complex wastewater, such as simultaneous containing oils, dyes and heavy metal ion, remains challenging. In this work, a cellulose-based photocatalytic ENM, is constructed for this purpose. The hybrid ENM is prepared via electrospinning deacetylated cellulose acetate/polyvinyl pyrrolidone (CeP) nanofibers as skeleton cores and in-situ synthesis of beta hydroxyl oxidize iron decorated iron-based MOF (β-FeOOH@MIL-100(Fe)) heterojunctions as photocatalytic sheaths. The core-sheath structured ENM has ultrahigh MIL-100(Fe) loading (78 wt%), large surface areas (1105 m 2 /g) and well-dispersed β-FeOOH nanorods. Thanks to these porous and hydrophilic MIL-100(Fe), along with a robust photocatalysis-Fenton synergy from β-FeOOH@MIL-100(Fe), the as-prepared ENM shows outstanding performances with simultaneous high removal efficiency for oils (99.5 %), dyes (99.4 %) and chromium ion (Cr(VI)) (99.7 %). Additionally, the photocatalytic ENM can achieve a long-term reuse owing to its inherent self-cleaning function.